ACCIDENTAL INGESTION OF TOOTHBRUSH: AN UNUSUAL FOREIGN BODY - Rasheed, Muhammad Asif; Kashif, Ali; Naz, Aneeqa; Ali, Sikandar (Journal of Ayub Medical College Abbottabad, 2018)
Toothbrush is a rare foreign body to be ingested accidentally. The unusual shape of the toothbrush with no theoretical possibility of spontaneous passage mandates an interventional approach. If left untreated, it can lead to pressure necrosis, bleeding, perforation and ulceration. An endoscopic attempt in an expert clinic if available is the ideal approach. If failed, surgical management by laparoscope or mini laparotomy should be done. The evaluation for underlying psychiatric disorders like bulimia, schizophrenia or generalized eating disorder should be considered to prevent such recurrence. Here, we present a case of 55 years of age, male living a normal life with no known comorbid, who ingested accidentally a toothbrush two weeks prior to presentation and was managed at our surgical department after a failed endoscopic attempt. Keywords: Bulimia; Endoscopy; Foreign Bodies; Stomach